2018
DOI: 10.1111/adb.12710
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus mediates the modulation on cocaine self‐administration induced by ultrasonic vocalization playback in rats

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 49 publications
12
34
1
Order By: Relevance
“…This mirror our previous study showing that presentation of an unfamiliar peer after acquiring selfadministration alone induce positive ultrasonic vocalization and reduce self-administration (Giorla et al, 2018). In contrast, play back of negative USV transiently increase self-administration (Montanari et al, 2018). These results highlight the critical role of vocal communication in the influence of proximal social factors on drug consumption.…”
Section: Ultrasonic Vocalization and Drug Addictionsupporting
confidence: 88%
See 2 more Smart Citations
“…This mirror our previous study showing that presentation of an unfamiliar peer after acquiring selfadministration alone induce positive ultrasonic vocalization and reduce self-administration (Giorla et al, 2018). In contrast, play back of negative USV transiently increase self-administration (Montanari et al, 2018). These results highlight the critical role of vocal communication in the influence of proximal social factors on drug consumption.…”
Section: Ultrasonic Vocalization and Drug Addictionsupporting
confidence: 88%
“…In a recent study, we have shown that the playback of positive USV of a nonfamiliar rat can reduce cocaine intake (Montanari et al, 2018). This mirror our previous study showing that presentation of an unfamiliar peer after acquiring selfadministration alone induce positive ultrasonic vocalization and reduce self-administration (Giorla et al, 2018).…”
Section: Ultrasonic Vocalization and Drug Addictionsupporting
confidence: 82%
See 1 more Smart Citation
“…In impulsivity tasks, STN lesion consistently increased the rate of trial omissions and response latency Robbins, 1997, 1999a;Winstanley et al, 2005), which can be interpreted as decreased motivation (Robbins, 2002;Higgins and Silenieks, 2017) (Figures 3, 6). However, when assayed using classical FR or PR operant tasks, STN lesion either increased (Baunez et al, 2002(Baunez et al, , 2005Uslaner et al, 2008;Montanari et al, 2018) or did not change (Baunez et al, 2005;Bezzina et al, 2008;Winter et al, 2008) self-administration of food or sucrose. Decreased cocaine or ethanol taking is the predominantly reported effect of STN lesion (Baunez et al, 2005;Pelloux and Baunez, 2017;Pelloux et al, 2018).…”
Section: Stn-dbs Is Not Equivalent To Functional Inactivationmentioning
confidence: 87%
“…Results of STN lesion studies were more heterogeneous than with DBS, with increases (n = 6), decreases (n = 9), or no change in reward seeking (n = 6) being reported (Figures 3, 6). This heterogeneity cannot be completely explained by the type of reward used; STN-lesions had heterogeneous effects on responding for sucrose and food Robbins, 1997, 1999a;Baunez et al, 2002Baunez et al, , 2005Winstanley et al, 2005;Bezzina et al, 2008;Lardeux and Baunez, 2008;Uslaner et al, 2008;Winter et al, 2008), as well as for addictive drugs (Baunez et al, 2005;Lardeux and Baunez, 2008;Uslaner et al, 2008;Pelloux and Baunez, 2017;Montanari et al, 2018;Pelloux et al, 2018).…”
Section: Stn-dbs Is Not Equivalent To Functional Inactivationmentioning
confidence: 99%